Partnership : the modern law of trade, business and professional partnership in England and Wales - Blackett-Ord, Mark (Butterworths, 1997)
Designed specifically for the specialist solicitor, this text deals with the practical issues inherent in setting up, running and dissolving a partnership whilst at the same time pays due regard to the long standing authority upon which the law in this area is founded.